Evaluation of Occupational Exposure of Glazers of a Ceramic Industry to Cobalt Blue Dye - Fatemeh Kargar; Seyed Jamaleddin Shahtaheri; Farideh Golbabaei; Abolfazl Barkhordari; Abbas Rahimi-Froushani; Monireh Khadem (Tehran University of Medical Sciences, 2013)
Background: Cobalt is one of the most important constituent present in ceramic industries. Glazers are the relevant workers when they are producing blue colored ceramic, causing occupational exposure to such metal. Through this study, urinary cobalt was determined in glazers in a ceramic industry when they were producing blue-colored ceramic glazes.Methods: In this case-control study, spot urine samples were collected from 49 glazers at the start and end of work shifts (totally 98 samples) in 2011. Control group were well matched for age, height, and weight. A solid phase extraction system was used for separation and preconcentration of samples followed by analysis by inductively coupled plasma-atomic emission spectroscopy (ICP-AES).All participants filled out a self administered questionnaire comprises questions about duration of exposure, work shift, use of mask, skin dermatitis, kind of job, ventilation system, overtime work, age, weight, and height. The lung function tests were performed on each control and cobalt exposed subjects. Analysis of covariance (ANCOVA) was used to evaluate the obtained results.Results: Urinary levels of cobalt were significantly higher in the glazers compared to the control group. There were significant differences at urinary concentration of cobalt at the start and end of the work shift in glazers. Spirometric parameters were significantly lower in the glazers compared to the control group. Among the variables used in questionnaire the significant variables were dermatitis skin, mask, ventilation, and overtime work.Conclusion: This study verified existence of cobalt in the urine glazers, showing lower amount than the ACGIH standard.